Hemādri, urpha, Hemāḍapanta yācẽ caritra : Devagirīcyā Yādava-rājañcyā itihāsāsaha - Pādhye, Keśava Āppā, d. 1948 (SAMP early 20th-century Indian books project ;, 1931)
Biography of Hemādri, minister in the court of the Yadavas of the Deccan.